Efficacy and Safety of Panax Notoginseng Saponins (Xueshuantong) in Patients With Acute Ischemic Stroke (EXPECT) Trial: Rationale and Design - Feng, Luda; Han, Fang; Zhou, Li; Wu, Shengxian; Du, Yawei; Zhang, Dandan; Zhang, Chi; Gao, Ying (Frontiers in Pharmacology, 2021)
Background: Although revascularization treatment is recommended as the first-line therapy for patients with non-minor acute ischemic stroke (AIS), it only benefits a minority of patients. Previous studies reported positive effects of Panax notoginseng saponins (PNS) (Xueshuantong lyophilized powder) on AIS, however, there have been no rigorous trials. This study will aim to assess the efficacy and safety of PNS therapy for patients with AIS. Methods: The Evaluation of Xueshuantong in Patients with acutE ischemiC sTroke (EXPECT) trial is a multicenter, randomized, placebo-controlled, double-blind study aiming to enroll 480 patients in China. Eligible patients with AIS within 72 hours of symptom onset will randomly receive either PNS or PNS placebo for 10 days and subsequently be followed up to 90 days. The primary outcome is the change in the National Institute of Health Stroke Scale (NIHSS) score from baseline to 10 post-randomization days. The secondary outcomes will be early neurological improvement (proportion of patients with NIHSS score 0-1), and Patient-Reported Outcomes Scale for Stroke score at 10 post-randomization days, the proportion of patients with life independence (modified Rankin Scale score of 0-1), proportion of patients with a favorable outcome (Barthel Index ≥ 90), and Stroke-Specific Quality of Life score at 90 days. Adverse events or clinically significant changes in vital signs and laboratory parameters, regardless of the severity, will be recorded during the trial to assess the safety of PNS. Conclusion: To our knowledge, this study is the first double-blind trial to assess the efficacy and safety of PNS in patients with AIS. Findings of the EXPECT trial will be valuable to improve evidence regarding the clinical application of PNS therapy in patients with AIS ineligible for revascularization treatment in the reperfusion era. Trial registration: This trial was registered with Clinicaltrials.gov (Unique identifier: NCT04415164).